Dpointgroup: the international experience in the B2B market - Lopes, Rita Santos (2021)
The internship report aims to be the final part of the Master’s degree within the Intercultural Studies for Business course taught at ISCAP. This is the report of an internship which took place from 2nd march until 31st july in the Spanish company Dpointgroup in the Marketing and International Relations department, during my Erasmus in Barcelona. This way, it will be presented the work developed during these months and as well as its analysis and reflection. This report will also demonstrate the history and characterization of the company and its strategies implemented using B2B marketing. To understand these strategies, this concept will be studied and related with the ones referred previously. With the development of this work, I could analyze my work and experience in Dpointgroup. Also, with this research I could conclude how culture, intercultural communication and interculturalism/multiculturalism play such a fundamental role in the international corporate environment.